Effects of MAPP Compatibilization and Acetylation Treatment Followed by Hydrothermal Aging on Polypropylene Alfa Fiber Composites - Noura Hamour; Amar Boukerrou; Hocine Djidjelli; Jean-Eudes Maigret; Johnny Beaugrand (International Journal of Polymer Science)
This work investigates the effect of hydrothermal aging on the properties of polypropylene/alfa fiber composites. Hydrothermal aging was induced in an environmental testing chamber at 65°C and 75% relative humidity (RH) over a 1000 h period. At the beginning (t=0 h), the results showed that Young’s moduli of the untreated alfa fibers and the acetylation-treated fibers increased by 21% and 36%, respectively, compared with the virgin polypropylene (PP). Additionally, Young’s moduli decreased by 7% for the compatibilized composites composed of maleic anhydride grafted polypropylene (MAPP). After 1000 h of aging, Young’s moduli decreased by 36% for untreated alfa fibers and 29% for the acetylation-treated alfa fibers and the compatibilized composites. Significant degradation was observed in the untreated alfa fiber samples. The Fourier transformed infrared (FTIR) allows us to distinguish the characteristic absorption bands of the main chemical functions present in the composite material before and after aging. The thermal properties showed that the thermal stability and the degree of crystallinity of the composites decreased after hydrothermal aging; this result was corroborated by the dynamical mechanical analysis (DMA) results.